2013
DOI: 10.1074/jbc.m113.479147
|View full text |Cite
|
Sign up to set email alerts
|

Array-assisted Characterization of a Fucosyltransferase Required for the Biosynthesis of Complex Core Modifications of Nematode N-Glycans

Abstract: Background:The chitobiose region of nematode N-glycans can be modified with three fucose residues. Results: Glycan arrays and other analytical techniques facilitated the definition of the biologically relevant activity of Caenorhabditis FUT-6. Conclusion: The concerted action of Caenorhabditis FUT-1, FUT-6, and FUT-8 is required for trifucosylation of worm N-glycan cores. Significance: New approaches for studying glycans from parasitic nematodes are now possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 52 publications
(58 reference statements)
0
36
0
Order By: Relevance
“…2A). C. elegans fut-8 (ok2558) as well as the double mutants fut-6(ok475)fut-1(ok892) and fut-6(ok475);fut-8(ok2558), lacking fucose residues linked to the GlcNAc units of the N-glycan core (22)(23)(24), were equally susceptible toward Lb-Tec2 as the wild-type strain. We therefore concluded that α1,3-or α1,6-linked core fucose was not required for Lb-Tec2-induced nematotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…2A). C. elegans fut-8 (ok2558) as well as the double mutants fut-6(ok475)fut-1(ok892) and fut-6(ok475);fut-8(ok2558), lacking fucose residues linked to the GlcNAc units of the N-glycan core (22)(23)(24), were equally susceptible toward Lb-Tec2 as the wild-type strain. We therefore concluded that α1,3-or α1,6-linked core fucose was not required for Lb-Tec2-induced nematotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The six glycans G1-G6 were immobilized in different subarrays on NHS activated glass slides and individual wells incubated with bovine milk β-1,4 galactosyltransferase 2.4.1.22 (GalT), C. elegans β-1,4 Nacetylgalactosaminyltransferase (GalNAcT), Arabidopsis thaliana core type α-1,3 fucosyltransferase (AtFucTA), C. elegans core type α-1,3 fucosyltransferase (CeFUT1), C. elegans α-1,3 fucosyltransferase (CeFUT6) and C. elegans core type α-1,6 fucosyltransferase (CeFUT8). [22][23][24][25][26] The presence of enzymatically extended structures was verified by incubating wells with the fluorescently tagged lectins, Ricinus communis (RCA-I), Wisteria floribunda (WFL) and Aleuria aurantia (AAL-555) that specifically recognize β-galactose, N-acetylgalactosamine and α-fucose, respectively. 27 With the exception of CeFUT6, enzymatic elongations of xylosylated glycans were possible as long as other previously reported basic structural requirements were fulfilled.…”
Section: Resultsmentioning
confidence: 99%
“…However, up to four fucose residues have been detected on C. elegans N-glycans and the exact nature of the linkage of the fourth fucose has remained obscure (3,12-14). Combined with the latest knowledge regarding the specificity of C. elegans core fucosyltransferases (13,15,16) as well as the exact structures of N-glycans from C. elegans and other nematodes (17), we concluded that some models for the tri- and tetrafucosylated N-glycans were incorrect. By preparing a triple mutant unable to core fucosylate its N-glycans, we generated a C. elegans strain containing maximally one fucose residue on the N-linked oligosaccharides.…”
Section: Introductionmentioning
confidence: 98%